Wrecked Emigrant Ships in The Bahamas: The Wreck of the Barque William and Mary - Lawlor, Jim (International Journal of Bahamian Studies, 2021)
The Bahamian archipelago is strategically located between the Atlantic and the Caribbean Sea. However, the hidden reefs and shoals, the changing sandbanks, and the unpredictable winds and currents, especially in the hurricane months, all conspired to make Bahamian waters the terror of navigators and the delight of wreckers during the age of sail. This article explores the wrecks of four emigrant ships in The Bahamas in the early 1850s. The European passengers were leaving poverty-stricken Europe to pursue the ‘American Dream’ but did not reach their destination without enduring the combined perils of weather and the hazards of Bahamian waters. Fortunately, they were rescued by humane Bahamian wreckers and assisted by inhabitants of Nassau and Governor Gregory, who organized their onward journey. In particular, the wreck of the William and Mary exposes the greed and lack of care that ship owners and captains showed in attempting to carry hapless passengers from Europe to the United States of America.